2023
DOI: 10.1007/s00520-023-07762-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring participant perceptions of a virtually supported home exercise program for people with multiple myeloma using a novel eHealth application: a qualitative study

Abstract: Introduction Supervision, tailoring, and flexibility have been proposed as key program elements for delivering successful exercise programs for people with multiple myeloma (MM). However, no studies to date have evaluated the acceptability of an intervention employing these components. The aim of this study was to determine the acceptability of a virtually supported exercise program and eHealth application for people with MM. Methods A qualitative description approach w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The exercises were able to be tailored to each individual within the group, allowing people of mixed abilities to take part together. Similar themes were identified in a study exploring participant perceptions of virtual exercise for people with multiple myeloma 49 who found that programmes should use tailoring, active support and employ personnel to run the sessions who were both knowledgeable and empathetic. Patients perceived that the instructor was important to help motivate the group and generate a peer-supportive environment, which has previously been highlighted as being important for people living with cancer.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The exercises were able to be tailored to each individual within the group, allowing people of mixed abilities to take part together. Similar themes were identified in a study exploring participant perceptions of virtual exercise for people with multiple myeloma 49 who found that programmes should use tailoring, active support and employ personnel to run the sessions who were both knowledgeable and empathetic. Patients perceived that the instructor was important to help motivate the group and generate a peer-supportive environment, which has previously been highlighted as being important for people living with cancer.…”
Section: Discussionmentioning
confidence: 55%
“…Patients perceived that the instructor was important to help motivate the group and generate a peer-supportive environment, which has previously been highlighted as being important for people living with cancer. 49 Patients were recruited across a range of levels of deprivation, and many lived a long distance from the treating hospital so the virtual nature of the programme enabled them to take part, removing barriers related to transport and costs. These benefits have been highlighted in other studies 27 28 49 and were confirmed by our qualitative findings.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile apps promoting physical activity can improve cancer-related fatigue, sedentary lifestyle, and psychosocial outcomes [121], also through personalized home exercise programs [122,123]. As cancer mortality declines, digital interventions delivering physical exercise interventions for cancer survivors are of equal importance [124].…”
Section: Cancermentioning
confidence: 99%